Physiotherapy Management in Meniscus Injury - Sari, Made Ayu Indah Puspa; Kurniawati, Ida (Kinetic and Physiotherapy Comprehensive, 2022)
Background: Meniscus injury is one of the most common knee injuries in the orthopedic field. This injury often occurs in sports that involve rotating movements, squats/excessive knee joint flexion such as in basketball, soccer or badminton. The medial meniscus is injured more often than the lateral meniscus, and this is due to the tight attachment of the meniscus to the medial collateral ligament of the knee joint, which limits its movement. Injury occurs when the femur rotates about the tibia, or the tibia against the femur, with the knee joint slightly flexed and supporting body weight.   Objective: This study aims to summarize secondary data related to meniscus injuries.   Methods: The research method used was a literature study using secondary data in the form of journals related to the topic of meniscus injury obtained through Google Scholar, Science Direct, and PubMed.   Results: Several studies have shown that someone with a knee injury can be given physiotherapy intervention in the form of exercise that is tailored to the symptoms experienced.   Conclusion: Based on the results of a literature review, neuromuscular and strengthening exercises, Mulligan's squeeze technique with conventional therapy, open and closed kinematic chain and education can improve symptoms after meniscus injury.